2021
DOI: 10.1097/sla.0000000000005254
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal Versus Extracorporeal Anastomosis in Robotic Right Colectomy

Abstract: Objective: To determine if minimally invasive right colectomy with intracorporeal anastomosis improves postoperative recovery compared to extra-corporeal anastomosis. Background: Previous trials have shown that intracorporeal anastomosis improves postoperative recovery; however, it has not yet been evaluated in a setting with optimized perioperative care or with patient-related outcome measures. Methods: This was a multicenter, triple-blind, randomized clinical trial at two high-volume colorectal centers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…For example, the oversewing of double stapled anastomosis has been shown to be protective for anastomotic leak ( P = 0.03), 21 however, this information is currently not available in the BCOR. Intra‐corporeal anastomotic techniques have also been associated with faster return of bowel function, although with no difference in length of stay or complication rates such as anastomotic leak or post‐operative bleeding 26–29 . These factors may be of interest in future analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the oversewing of double stapled anastomosis has been shown to be protective for anastomotic leak ( P = 0.03), 21 however, this information is currently not available in the BCOR. Intra‐corporeal anastomotic techniques have also been associated with faster return of bowel function, although with no difference in length of stay or complication rates such as anastomotic leak or post‐operative bleeding 26–29 . These factors may be of interest in future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-corporeal anastomotic techniques have also been associated with faster return of bowel function, although with no difference in length of stay or complication rates such as anastomotic leak or post-operative bleeding. [26][27][28][29] 29 These factors may be of interest in future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that that ICA has advantages over ECA such as shorter length of incision, less estimated blood loss, and shorter time to bowel function recovery ( 2 , 17 , 18 ). However, two recent high-quality randomized controlled trials ( 8 , 19 ) and one study on robotic left colectomy ( 20 ) failed to show that outcomes after ICA were better than after ECA. The advantages of the KHEA technique could be a further argument in favor of the ICA technique.…”
Section: Discussionmentioning
confidence: 99%
“…Left hemicolectomy may sometimes be a complex procedure [mobilization of the splenic flexure, unexpected adhesions or tumor invasion, intraoperative vascular problems (5,6). Complete laparoscopic colectomy with an intracorporeal reconstruction technique requires advanced surgical skills and may increase operation time, hospitalization costs, and/or the risk of abdominal contamination (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The literature currently reports multiple benefits of intracorporeal anastomosis compared to extracorporeal anastomosis, for example earlier recovery of bowel function, less postoperative pain, utility in obese patients with shortened mesentery, clear visualization of bowel orientation, and equivalent anastomotic leak and 30‐day morbidity rates. [1–4]…”
Section: Videomentioning
confidence: 99%